For love or for money? A study of the marriage wage premium in Colombia (2016)
Being married may raise worker productivity and increase the probability of remaining in a job and, as consequence, obtaining a wage premium -- Yet, this effect may be different for males and females -- In developing countries, such as Colombia, the premium may be larger than in developed countries due to the differing social norms and labor market structures -- Using cross-sectional data from Colombian Household Surveys, this paper examines the marriage wage premium and its evolution in Colombia both at the aggregate level and by gender -- We find a marriage wage premium for both male and female populations; this wage premium is explained by the greater human capital endowment in married people and to employer favoritism due to the “social norms” which consider being married an appropriate behavior and reward it